1999
DOI: 10.1038/sj.cdd.4400529
|View full text |Cite
|
Sign up to set email alerts
|

CD14 is a component of multiple recognition systems used by macrophages to phagocytose apoptotic lymphocytes

Abstract: Expression of the aminophospholipid phosphatidylserine (PS) on the surface of apoptotic lymphocytes and lipidsymmetric erythrocytes triggers their phagocytosis by macrophages. Phagocytosis by both activated and unactivated macrophages, which utilize different recognition systems, can be blocked by certain monoclonal antibodies directed against the LPS receptor, CD14. Here we investigate the requirement for CD14 in the phagocytosis of both apoptotic thymocytes and lipid-symmetric erythrocytes by both activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
45
1

Year Published

2000
2000
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 20 publications
1
45
1
Order By: Relevance
“…8,10 Phagocytosis by both recognition systems is inhibited by treating macrophages with antibodies to the lipoprotein receptor CD36 11 and to the lipopolysaccharide receptor CD14. 12,13 However, the ligands which any of the receptors may recognize on the apoptotic cell surface have yet to be identified. In contrast, ICAM-3 on the lymphocyte surface participates in the interaction of apoptotic lymphocytes and unactivated macrophages, although the receptor with which ICAM-3 interacts has not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…8,10 Phagocytosis by both recognition systems is inhibited by treating macrophages with antibodies to the lipoprotein receptor CD36 11 and to the lipopolysaccharide receptor CD14. 12,13 However, the ligands which any of the receptors may recognize on the apoptotic cell surface have yet to be identified. In contrast, ICAM-3 on the lymphocyte surface participates in the interaction of apoptotic lymphocytes and unactivated macrophages, although the receptor with which ICAM-3 interacts has not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…CD14 seems to be required for phagocytosis of lymphocytes and necessary for phagocytosis of lipid-symmetric erythrocytes both by non-activated and activated macrophages. 1 Since phagocytosis of apoptotic lymphocytes by macrophages is stereospecifically inhibited by phosphatidyl-Lserine liposomes, a specific receptor may be involved in PS recognition. 18 This PS-receptor has not been clearly defined yet, however, CD14, CD68, CD36 19 have been proposed as candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a non-specific lipid flipsite, termed scramblase, is activated resulting in an accelerated PS flip-flop. 1 It is well established that PS serves as recognition signal for the clearance of apoptotic cells. 2 ± 5 In a recent publication it was shown that preincubation of apoptotic lymphocytes with AxV efficiently blocked the uptake of apoptotic cells by murine peritoneal macrophages, macrophages of the mouse J774 cell line and bone marrow macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Many receptors, including C1q and lectin receptors (5), scavenger receptors such as CD68 (6) or CD36 associated with ␣ v ␤ 3 or ␣ v ␤ 5 vitronectin receptors (7,8), CD14 (9,10), and the recently cloned phosphatidylserine (PS) 4 receptor (11) have been reported to mediate the binding and uptake of apoptotic cells by macrophages. The most characteristic surface change on apoptotic cells is the loss of phospholipid bilayer asymmetry and the exposure of oxidized PS on the outer leaflet of the plasma membrane (12)(13)(14)(15)(16), the latter change being absolutely required for recognition and engulfment to occur (2,16).…”
mentioning
confidence: 99%